2019
DOI: 10.1038/s41598-019-54754-2
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin-pregnane X receptor-JNK axis accelerates skin wound healing

Abstract: Indirubin is a potent anti-inflammatory phytochemical derived from indigo naturalis. It is also endogenously produced in the intestine and detected in the circulation in mammals. Indirubin exerts its biological functions via two xenobiotic receptor systems: aryl hydrocarbon receptor (AHR) and pregnane X receptor (PXR); however, its effects on wound healing remain elusive. To investigate whether indirubin promotes wound healing, we utilized an in vitro scratch injury assay and in vivo full-thickness mouse skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…In addition, biological processes and pathway enrichment (GO, KEGG, and WIKI) identified a number of molecular functions and pathways that may be relevant for MH including the pregane X receptor (PXR)-JNK axis, which has been shown to be involved in healing in other organ such as skin. 54 Constitutive androstane receptor (CAR) pathway regulates intestinal mucosal response to injury 55 in mice. Activation of PXR, which is a close relative of CAR, may also enhance intestinal epithelial wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, biological processes and pathway enrichment (GO, KEGG, and WIKI) identified a number of molecular functions and pathways that may be relevant for MH including the pregane X receptor (PXR)-JNK axis, which has been shown to be involved in healing in other organ such as skin. 54 Constitutive androstane receptor (CAR) pathway regulates intestinal mucosal response to injury 55 in mice. Activation of PXR, which is a close relative of CAR, may also enhance intestinal epithelial wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these pathways, this study identified several metabolic pathways including those involving arachidonic acid, amino acids, terpenoid biosynthesis, and the TCA cycle, whose involvement in healing is already recognized. 51 , 53 , 54 Interestingly, the involvement of amino acids histidine and arginine in intestinal cell restitution may also involve TGF-β pathways. 58 Transforming growth factor-β promotes protein translation at least in part by increasing the mitochondrial oxidation of glucose and glutamine carbons to support the energy demand of translation.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as reported previously [ 46 ]. The antibodies used were as follows: rabbit anti-human NECTIN4 (1:1000, Abcam; ab192033), rabbit anti-human Akt (1:1000, #9272), rabbit anti-human phospho-Akt (1:2000, #4060), rabbit anti-human ERK (1:1000, #9102), rabbit anti-human phospho-ERK (1:2000, #4370), rabbit anti-human MEK (1:1000, #9122), rabbit anti-human phospho-MEK (1:1000, #9154), rabbit anti-human EGFR (1:1000, #4267), rabbit anti-human β-actin (1:2000, #4970), and goat anti-rabbit IgG horseradish peroxidase-linked secondary antibody (1:10,000, #7074) (all from Cell Signaling Technologies, Danvers, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…•EGF [11,12] •Pep19-2.5 [13] •Hepatocyte Growth Factor (HGF) [14] •micro RNA 21 [15] •ERBB2 [16] •Keratinocyte Growth Factor (KGF) [17] •AES16-2M (ERK activating peptide) [18] •GFP-Smad2 [19] •Lipofectamine and KGF-mRNA [17] •SIS3 (Smad3 phosphorylation specific inhibitor) [19] •Liraglutide, a Glucagon-like peptide-1 analogue (concentration dependent) [20] •Thrombin [21] •AHR siRNA [22] •EGF receptor inhibitor (EGFRi) [19] •JNK inhibitor (JNKi) [19] •MEK1 inhibitor (MEKi) [19] •Enhanced green fluorescent protein (eGFP) with Lipofectamine [17] •LY 294002 (PI3K inhibitor) [20] •IDR-1018, a synthetic innate defense regulator peptide, in normoxia [23] •EGFR antagonist (AG1478) [21] •ERK1/2 antagonist (UO126) [21] •AHR antagonist, CH223191 [22] •RIPK4 via TGFβ [24] •ERBB3 [16] •ERK inhibitor (U0126) [18] •IDR-1018 in hypoxic condition [23] •ALK5 (TGF-ß receptor I) inhibitor (TGFRi) [19] •Cytochalasin D [22] •PXR siRNA [22] •PXR antagonist, SPA70 [22] •JNK inhibitor (SP600125 and indirubin) [22] Natural Products…”
Section: Decrease No Impactmentioning
confidence: 99%